1984
DOI: 10.1093/oxfordjournals.aje.a113878
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptive Use and Fibrocystic Breast Disease Among Pre- And Postmenopausal Women1

Abstract: The association between use of oral contraceptives and fibrocystic breast disease was assessed among women aged 20-74 years in a hospital-based case-control study conducted between November 1979 and November 1981 in Connecticut. The study groups comprised 633 women with biopsy-proven fibrocystic breast disease and 1,062 controls who had been admitted, as inpatients or outpatients, to general surgical services. For the premenopausal women, there was no evidence that long-term use of oral contraceptives was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…It has been noted that the negative association of body weight with BBD may be diagnostic artifact, rather than obesity being protective (Ernster, 1981). Use of oral contraceptives was not protective, in accord with recent reports (Berkowitz et al, 1984).…”
supporting
confidence: 76%
“…It has been noted that the negative association of body weight with BBD may be diagnostic artifact, rather than obesity being protective (Ernster, 1981). Use of oral contraceptives was not protective, in accord with recent reports (Berkowitz et al, 1984).…”
supporting
confidence: 76%
“…Results from those studies which have collected such data have been inconsistent. Two studies (Royal College of General Practitioners, 1977;Brinton et al, 1981) showed an inverse association between the dose of the progestogenic component and risk of BBD (while holding the dose of the oestrogenic component constant), one (Berkowitz et al, 1984a) showed an increase in risk of BBD in those who had used combined preparations with relatively low oestrogenic and progestogenic content and in those who had used sequential preparations or preparations containing progestin only, and one showed some suggestion of a reduction in risk in those who had used sequential preparations. These apparently contradictory findings may provide further indication of the uncertainty that exists over the effects of combinations of oestrogens and progestogens on mammary epithelial proliferation rates.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to reconcile these apparently contradictory observations, Hsieh et al (1984) suggested that use of oral contraceptives might suppress the symptoms of BBD and thereby decrease the likelihood of its detection, without influencing the underlying BBD pathology, while Cole (1977) drew attention to the difference in breast cancer risk according to histological subtype of BBD, and postulated that oral contraceptives might be associated with reduced risk of those forms of BBD not associated with increased breast cancer risk, but with increased risk of those forms of BBD associated with increased risk of breast cancer. To date, however, investigation of the former of these possibilities has been limited to adjustment of estimates of association for breast self-examination and indices of medical care utilization (Berkowitz et al, 1984a;Rohan et al, 1992), while the hypothesis of Cole (1977) has been investigated only in case-control studies, the results of which have been inconsistent (LiVolsi et al, 1978;Kampert et al, 1983;Pastides et al, 1983;Berkowitz et al, 1984a;Hsieh et al, 1984). In the cohort study reported here, which was conducted in a population screened (to a variable extent) for breast disease, we investigated the association between use of oral contraceptives and risk of BBD overall, and by histological subtype.…”
mentioning
confidence: 99%
“…The data were drawn from a case-control study comparing characteristics of women aged 20-74 with a biopsy-proven diagnosis of fibrocystic breast disease to characteristics of women in the same age range with other surgical conditions (Berkowitz et al, 1984). The pathology records of five Connecticut hospitals were used to identify women with a presumptive diagnosis of fibrocystic breast disease during the period November 1979 to November 1981.…”
Section: Methodsmentioning
confidence: 99%
“…The respective values of K for the intraobserver reliability were 0 . 8 9 ,~ <O.OoOl and0.62, In the analysis, women were stratified by menopausal status (Berkowitz et al, 1984). Accordingly, 450 cases and 663 controls were classified as premenopausal, 40 cases and 44 controls as perimenopausal, and 143 cases and 355 controls as postmenopausal.…”
Section: Methodsmentioning
confidence: 99%